Protein homeostasis in mitochondria: AAA+ chaperones & proteases - Dougan, David A. (Henry Stewart Talks, 2012)
Protein homeostasis in mitochondria, Mitochondria play an important role in ageing and disease, Quality control of mitochondria is controlled at three different levels, Protein quality control (PQC) in mitochondria is maintained by mitochondrial chaperones and AAA+ proteases, Following proteotoxic stress a specific mitochondrial unfolded protein response (mtUPR) is activated, The AAA+ protease CLPXP is proposed to play a key role in mtUPR signaling, A novel mtCLPX interacting protein that modulates the activity of mtCLPXP both in vitro and in vivo has been identified